Immune Response to Hepatitis B Virus Vaccine in Term and Preterm Babies Received as per EPI Schedule - Dey, Sanjoy Kumer; Nahar, Zakia; Chowdhury, Suparna; Shahidullah, M; Rahman, Shahana A (Bangladesh Journal of Child Health, 2010)
Objective: To determine the immune response of hepatitis B virus (HBV) vaccine given according to EPI schedule and to compare the antibody response among term and preterm babies. Setting: EPI centre, Paediatric OPD and Department of Virology, Bangabandhu Sheikh Mujib Medical University (BSMMU). Duration: May 2006 to April 2007. Study Population: Thirty preterm and thirty term babies who received 3 doses of HBV vaccination according to EPI schedule. Outcome variables: Immune response to HBV vaccine according to gestational age, according to birth weight and comparison of immune response among term and preterm babies. Results: Thirty three percent infants were non-responder in all the groups and 50% infants were good responders in 34-36 weeks and above. Total response was 80% among preterm and 86.6% among term infants. Conclusion: Most of the infants showed positive immune response and there was no significant difference among term and preterm babies. Key words: Efficacy of HBV vaccine; immune response; poor responder; good responder. DOI: 10.3329/bjch.v33i1.5668 Bangladesh Journal of Child Health 2009; Vol.33(1): 1-5